2018
DOI: 10.1002/jmv.25031
|View full text |Cite
|
Sign up to set email alerts
|

The antimalarial drug amodiaquine possesses anti‐ZIKA virus activities

Abstract: Zika virus (ZIKV) outbreak has emerged as a global health threat, particularly in tropical areas, over the past few years. No antiviral therapy or vaccine is available at present. For these reasons, repurposing clinically approved drugs against ZIKV infection may provide rapid and cost-effective global health benefits. Here, we explored this strategy and screened eight FDA-approved drugs for antiviral activity against ZIKV using a cell-based assay. Our results show that the antimalarial drug amodiaquine has an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 41 publications
0
40
0
Order By: Relevance
“…Aminoquinolines were proposed for the treatment of other viral infections, such as ZIKV. In 2017, it was demonstrated that CQ and AQ exerted anti-ZIKV activity in Vero cells, with low micromolar IC 50 s [140]. These results were in agreement with the decreasing number of ZIKV-infected cells after CQ treatment.…”
Section: Chloroquine and Hydroxychloroquine And Emerging Virusesmentioning
confidence: 62%
See 1 more Smart Citation
“…Aminoquinolines were proposed for the treatment of other viral infections, such as ZIKV. In 2017, it was demonstrated that CQ and AQ exerted anti-ZIKV activity in Vero cells, with low micromolar IC 50 s [140]. These results were in agreement with the decreasing number of ZIKV-infected cells after CQ treatment.…”
Section: Chloroquine and Hydroxychloroquine And Emerging Virusesmentioning
confidence: 62%
“…Flaviviridae BVDV(surrogate HCV) Artemisinin in vitro [187,188] Dihydroartemisinin in vitro [63] HCV Artemisinin in vitro [20][21][22] Artesunate in vitro [57] Chloroquine in vitro [148][149][150] ZIKV Mefloquine in vitro [130,131] Chloroquine in vitro [140,141] Amodiaquine in vitro [140] Atovaquone in vitro [166] DENV Quinine sulfate in vitro [66] Mefloquine in vitro [131] Halofantrine in vitro [134] Doxycycline in vitro [168,178] Amodiaquine in vitro [162] CHIKV Doxycycline in vitro [169] Chloroquine in vitro [37,138,139] Atovaquone in vitro [166] Togaviridae SFV Halofantrine in vitro [134] Rhabdoviridae VSV Doxycycline in vitro [170] Orthomyxoviridae IAV Quinine sulfate in vitro [70] In vivo (mouse) [67] Mefloquine in vitro [70] Doxycycline in vivo (mouse) [171] Chloroquine in vitro [159]…”
Section: Virus Family Virus Species Drug Type Of Study (Model) Referementioning
confidence: 99%
“…Despite current potential protection due to herd and selfimmunity, environmental factors, and host-vector-virus interactions that keep ZIKV at low incidence (1,55,56), preventing ZIKV and other arbovirus infections should be a priority. In recent years, many compounds have been proposed as potential anti-ZIKV agents following in vitro results (29,30,(57)(58)(59)(60)(61)(62)(63)(64)(65)(66). Some of these drugs have an extensive background in the medical field and offer attractive options, either alone or in combination, for treatment and perhaps prophylaxis of ZIKV infections; however, most of them remain inadequate to be used during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite current potential protection from herd and self-immunity, environmental factors, and host-vector-virus interactions that keep ZIKV in the low incidence figures [1], [52], [53], [54], [55], preventing ZIKV and other arbovirus infections should be a priority. In recent years, many compounds have been proposed as potential anti-ZIKV agents following in vitro results [24], [25], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65]. Some of these drugs have an extensive background in the medical field and offer attractive options, either alone or in combination, for treatment and perhaps prophylaxis of ZIKV infections; however, most of them remain inadequate to be used during pregnancy.…”
Section: Discussionmentioning
confidence: 99%